Antiretroviral treatment-associated labia majora lipohypertrophy: a rare case and plastic surgical treatment options / Akmal Hisham … [et al.] - Hisham, Akmal; Ilenghoven, Devananthan; Wan Ahmad Kamal, Wan Syazli; Ibrahim, Salina; Mohd Yussof, Shah Jumaat (Universiti Teknologi MARA Cawangan Selangor, 2017)
The emergence of highly active antiretroviral therapy (HAART) has revolutionized the prognosis of HIV-infected patients. However, the extended use of HAART is associated with a disfiguring complication termed lipodystrophy, a disorder of body fat maldistribution causing peripheral fat loss (lipoatrophy) and central fat accumulation (lipohypertrophy). Lipoatrophy commonly affects the face, legs, buttocks and arm, whilst lipohypertrophy frequently favours the abdomen, breast and dorsocervical region. To our knowledge, we present only the second documented case in the literature of a labia majora lipohypertrophy in a HIV-positive patient receiving long-term HAART. The severity of labial abnormality caused significant physical and functional morbidities. Labiaplasty with dermolipectomy of the labia majora and excisional lipectomy of the mons pubis was successfully performed. At a 6-month follow-up, patient had no recurrence with resolution of symptoms and resumption of normal activities of daily living (ADL).